Intrapersonal intelligence (Journal of Parents and Teachers, 2013)
This section of the magazine is about the intrapersonal intelligence which is enshrined inside the Multiple intelligences theory. The author provides a definition of this intelligence as the ability of knowing yourself and that implies certain capacities.  He also establishes three developmental lever of the intelligence, he proposes games that favor its development and presents a series of tools or attitudes that the people use thanks to this intelligence 8for example, emotions analysis or self-evaluation).  Finally, the author proposes activities to work with this intelligence transversally along the different areas.
Keywords: intrapersonal intelligence; self-evaluation; emotions; centerfold; education.